Application of fluorine-containing onium salt in electrolyte additive
By adding fluorinium salts to the electrolyte, the problem of dendrite growth during the charging and discharging of alkali metal batteries is solved, and the battery stability and circulation performance are improved, and the electrolyte with high flame retardant performance is provided.
Patent Information
- Application Number
- CN202510063912.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
Alkaline metal batteries are prone to form dendrites during repeated charging and discharging, resulting in loss of active materials, internal short circuits, thermal runaway, battery failure and explosion.
Fluorinium salt is used as an electrolyte additive, and its cations can enter the inner layer of Helmholtz in the lithium, sodium, and potassium negative electrodes, and are preferred to decompose into LiF-rich electrolytes, inhibit dendrites from growing, and enrich on the surface of the metal negative electrode, repelling metal ions deposition.
Effectively inhibit the growth of alkali metal dendrites, improve the stability of the negative electrode, improve the electrochemical performance of the secondary battery, and improve the circulation and flame retardant performance of the battery.
Smart Images

Figure CN119890449A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrolytes, and in particular relates to the application of a fluorine-containing onium salt in an electrolyte additive. Background Art
[0002] With the advent of the 21st century, energy problems are becoming increasingly severe, and environmental pollution continues to worsen. In order to achieve sustainable development, the utilization and development of new and renewable energy sources have become a hot topic of research in countries around the world. Hydropower, wind power, hydrogen power, nuclear power, tidal power, and solar power have been vigorously developed and utilized in countries around the world. The improvement of the performance of energy storage devices can effectively promote the popularization of new energy applications. Among the many energy storage devices, electrochemical energy storage batteries have become one of the important research directions in countries around the world due to their high energy density, good energy conversion efficiency, low pollution, and convenient combination and mobility.
[0003] Alkali metal batteries (lithium-ion batteries, sodium-ion batteries, potassium-ion batteries) are considered to be one of the most promising negative electrode materials for the next generation of high energy density batteries due to their ultra-high theoretical capacity (Li: 3860mAh / g, Na: 1166mAh / g, K: 687mAh / g) and low electrochemical potential (Li: -3.04V, Na: -2.71V, K: -2.93V relative to standard hydrogen electrode). However, the commercial application of alkali metal batteries is seriously hindered by the formation of dendrites during repeated charge and discharge, which leads to the loss of active materials. The growth of alkali metal dendrites can penetrate the diaphragm, causing internal short circuits, thermal runaway, and even catastrophic battery failure and explosion. In addition, alkali metal dendrites increase the side reactions between alkali metals and organic electrolytes, resulting in the continuous consumption of both. This consumption can lead to electrolyte drying, corrosion of alkali metal anodes, and even the production of electrochemically inert alkali metals, resulting in low Coulombic efficiency, fast capacity decay, and large polarization. Lithium-rich layered oxide cathode materials have extremely high energy density and have been widely used in consumer batteries and power batteries. The energy density of batteries matched with lithium anodes can reach 400Wh / kg, and they are considered to be one of the most promising energy storage battery systems. However, layered lithium-rich oxide batteries have a high voltage platform, high reaction activity, and are prone to combustion and explosion.
[0004] Therefore, how to provide an electrolyte that has flame retardant properties, is resistant to high voltage, and can inhibit the growth of alkali metal dendrites is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes the use of a fluorine-containing onium salt in an electrolyte additive.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A use of a fluorine-containing onium salt in an electrolyte additive, wherein the structure of the fluorine-containing onium salt is shown in formula (1):
[0008]
[0009] Wherein, R1 and R2 are independently selected hydrocarbon groups.
[0010] More preferably, the fluorine-containing onium salt comprises the following compounds:
[0011]
[0012]
[0013] Beneficial effects: The fluorine-containing onium salt cation can enter the Helmholtz inner layer of the lithium, sodium, potassium, and zinc negative electrode / electrolyte surface, preferentially decompose the electrolyte solvent into an electrolyte rich in LiF, and inhibit the growth of dendrites. In addition, when the metal negative electrode SEI film is broken and the fresh metal negative electrode is exposed, the fluorine-containing onium cation will be enriched on the exposed metal surface under the action of the electric field force and surface tension, repelling the metal ions from depositing on the exposed metal surface, further inhibiting the growth of metal dendrites.
[0014] An electrolyte additive comprises the above-mentioned fluorine-containing onium salt.
[0015] The invention discloses an application of an electrolyte additive in preparing an electrolyte.
[0016] An electrolyte comprises a solvent, an electrolyte salt and the electrolyte additive.
[0017] Beneficial effects: The fluorine-containing onium salt cation has a synergistic effect with the electrolyte salt and solvent, and will produce an electrolyte rich in LiF, Li2O, Li3N, and Li2CO3 on the surface of the metal negative electrode, inhibiting the growth of dendrites. In addition, when the metal negative electrode SEI film is broken and the fresh metal negative electrode is exposed, the fluorine-containing onium cation will be enriched on the exposed metal surface under the action of the electric field force and surface tension, repelling the deposition of metal ions on the exposed metal surface, further inhibiting the growth of metal dendrites.
[0018] Preferably, based on the total mass of the electrolyte being 100%, the content of the electrolyte additive is ≥ 0.1 wt%.
[0019] More preferably, the content of the electrolyte additive is 0.25wt%-30wt%.
[0020] More preferably, the content of the electrolyte additive is 1wt% to 5wt%, or 0.1wt% to 20wt%, or 0.5wt% to 15wt%, or 0.5wt% to 10wt%, or 0.5wt% to 8wt%, or 0.5wt% to 5wt%, or 1wt% to 8wt%, or 1wt% to 5wt%, or 1.5wt% to 8wt%, or 2wt% to 8wt%, or 2wt% to 7wt%, or 2wt% to 6wt%, or 2wt% to 5wt%.
[0021] More preferably, the content of the electrolyte additive is 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, or 10wt%.
[0022] Beneficial effects: When the content of fluorine-containing onium salt is low, the synergistic effect of fluorine-containing onium salt cations, electrolyte salts and solvents will produce electrolytes rich in LiF, Li2O, Li3N, and Li2CO3 on the surface of the metal negative electrode, inhibiting dendrite growth. However, when it is too high, it will lead to low electrolyte ion conductivity, thickening of SEI on the surface of the lithium negative electrode, a sharp increase in battery impedance, and poor battery performance. All are preferably 0.5-10%.
[0023] Preferably, the solvent includes an ether solvent, a carbonate solvent and a borate solvent.
[0024] Preferably, the ether solvent includes a cyclic ether or a chain ether, and the cyclic ether includes but is not limited to one or more of 1,3-dioxolane (DOL), 1,4-dioxolane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF);
[0025] The chain ether includes, but is not limited to, one or more of tetraethylene glycol dimethyl ether (TEGDME), dimethoxymethane (DMM), ethylene glycol dimethyl ether (DME), and 1,1,2,2-tetrafluoroethyl-2',2',2'-trifluoroethyl ether (TFTE).
[0026] The carbonate solvent includes cyclic carbonate or chain carbonate, and the cyclic carbonate includes but is not limited to one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), vinylene carbonate, propylene carbonate (PC), γ-butyrolactone (GBL), and butylene carbonate (BC);
[0027] The chain carbonate includes, but is not limited to, one or more of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dipropyl carbonate (DPC).
[0028] The borate ester solvent includes one or more of tri(2,2,2-trifluoroethyl) borate (TTFB), trimethyl borate, and triethyl borate.
[0029] Preferably, the solvent includes tetraethylene glycol dimethyl ether, fluoroethylene carbonate and tris(2,2,2-trifluoroethyl) borate.
[0030] Beneficial effects: Fluorinated solvents such as fluoroethylene carbonate and tris(2,2,2-trifluoroethyl) borate will synergize with fluorinated onium salts to produce a LiF-containing SEI film, inhibiting dendrite growth. In addition, tetraethylene glycol dimethyl ether and tris(2,2,2-trifluoroethyl) borate are high flash point solvents, and the fluorinated properties of fluoroethylene carbonate and tris(2,2,2-trifluoroethyl) borate can have a flame retardant effect.
[0031] Preferably, the electrolyte salt includes one or any several of MPF6, MBF4, MODFB, MBOB, MClO4, MNO3, MCF3SO3, MODFP, MN(SO2CF3)2, MN(SO2F)2, MHFDF, MTFSI, and MFSI;
[0032] Wherein, the M is one of Li, Na or K.
[0033] More preferably, the electrolyte salt includes LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), lithium difluorooxalatoborate (LiODFB) 、 LiBOB (lithium bis(oxalatoborate), LiClO4 (lithium perchlorate), LiNO3 (lithium nitrate), LiCF3SO3 (lithium trifluoromethanesulfonate), LiN(SO2CF3)2 (lithium bis(trifluoromethylsulfonyl)imide), LiN(SO2F)2, LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiFSI (lithium bis(fluorosulfonyl)imide), LiHFDF (lithium 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonic acid imide), LiTFSI (lithium bis(trifluoromethylsulfonyl)imide), NaTFSI (sodium bis(trifluoromethylsulfonyl)imide), KTFSI (potassium bis(trifluoromethylsulfonyl)imide), cyclic imide salts or any combination thereof;
[0034] The cyclic imide salt is selected from one or any combination of 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonic acid lithium imide, 1,1,2,2-tetrafluoroethane-1,3-disulfonic acid lithium imide, and 1,1,2,2,3,3,4,4-octafluorobutane-1,3-disulfonic acid lithium imide.
[0035] Beneficial effect: The fluorine-containing onium salt cation can cooperate with the above salts to generate a SEI film rich in MF and MCl, thereby inhibiting dendrite growth.
[0036] The invention discloses an application of an electrolyte in preparing a secondary battery.
[0037] Beneficial effects: The electrolyte can effectively inhibit dendrite growth, improve negative electrode stability, and thus improve the electrochemical performance of secondary batteries.
[0038] A secondary battery comprises the above electrolyte.
[0039] Preferably, the secondary battery further comprises a positive electrode, a negative electrode and a separator disposed between the positive electrode and the negative electrode.
[0040] More preferably, the positive electrode includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, the positive electrode active material includes but is not limited to at least one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, ternary positive electrode, and sulfur. The ternary material includes but is not limited to a nickel-cobalt-manganese compound.
[0041] The negative electrode includes a negative electrode material layer, and the negative electrode material layer includes a negative electrode active material. The negative electrode active material includes but is not limited to at least one of a graphite negative electrode, a silicon-carbon negative electrode, a single lithium, a single sodium, a single potassium, a single magnesium, a single aluminum, a single zinc, a lithium-containing complex, a sodium-containing complex, a potassium-containing complex, a magnesium-containing complex, an aluminum-containing complex, and a zinc-containing complex.
[0042] Preferably, the positive electrode material, the negative electrode material or the electrolyte of the secondary battery includes alkaline earth elements.
[0043] More preferably, the alkaline earth element is lithium;
[0044] More preferably, the lithium element may be a single lithium substance, a lithium-containing compound, a lithium-containing composite, etc. When the electrolyte contains the lithium element, the lithium element may be contained in the electrolyte of the electrolyte, or in the additive of the electrolyte. The lithium-containing battery includes but is not limited to a lithium-cobalt oxide battery, a lithium-sulfur battery, and a battery whose positive and negative electrode materials do not contain lithium. For example, by way of example but not limitation, it may be a sodium cobalt oxide battery containing sodium sodium in the electrolyte.
[0045] More preferably, the secondary battery is a lithium-cobalt oxide battery.
[0046] Beneficial effects: Fluorine-containing onium salts can generate LiF-rich SEI on the battery surface, hinder the continuous decomposition of the electrolyte, increase the voltage window of the electrolyte, inhibit the growth of lithium dendrites, and improve the battery cycle performance.
[0047] Compared with the prior art, the present invention has the following advantages and technical effects:
[0048] The present invention uses an onium salt containing fluorine on the cation as an electrolyte additive. Since the cation can easily reach the Helmholtz inner layer on the surface of the lithium negative electrode, it will decompose on the surface of the lithium negative electrode in preference to the solvent to form an electrolyte rich in LiF, inhibiting the growth of lithium dendrites. When the lithium dendrites break through the SEI film, the solvent of the electrolyte will further decompose. Since the solvent contains F, a secondary SEI film rich in LiF will be generated on the surface of the lithium dendrites after further decomposition, inhibiting the continuous growth of lithium dendrites. The synergistic effect of the solvent and the additive will effectively improve the stability of the lithium negative electrode. In addition, the solvent in the electrolyte provided by the present invention is a high flash point solvent and a F-rich solvent, so that the electrolyte has high flame retardancy. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0050] Figure 1 The LSV curves of the inert batteries obtained in Example 1 and Comparative Example 1 of the present invention are shown;
[0051] Figure 2 The coulombic efficiency diagram of the Li-Cu battery obtained in Example 2 of the present invention and Comparative Example 2;
[0052] Figure 3 The time-voltage curves of the Li-Li symmetric batteries obtained in Example 3 and Comparative Example 3 of the present invention;
[0053] Figure 4 This is a coulombic efficiency diagram of the LiCoO2-Li battery obtained in Example 4 of the present invention and Comparative Example 4;
[0054] Figure 5 The SEM images of the lithium electrodes of the Li-Li batteries obtained in Example 3 and Comparative Example 3 of the present invention after 100 cycles are shown. DETAILED DESCRIPTION
[0055] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0057] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0058] Unless otherwise specified, the room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.
[0059] In the following examples, the structural formula of the fluorine-containing onium salt is as follows:
[0060]
[0061] Example 1
[0062] An electrolyte comprising the following raw materials:
[0063] 0.8M lithium hexafluorophosphate (LiPF6), 0.2M lithium difluorobis(oxalato)phosphate (LiODFB), 0.4M lithium nitrate (LiNO3), 0.5wt% compound 1 ((diethylamino)difluorosulfonium tetrafluoroborate DDTB) and solvent;
[0064] The solvent is tetraethylene glycol dimethyl ether (TGDME): fluoroethylene carbonate (FEC) and tris (2,2,2-trifluoroethyl) borate (TTFB) mixed in a volume ratio of 7:2:1.
[0065] An inert battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a stainless steel gasket and the negative electrode is a stainless steel gasket.
[0066] Performance test: The battery was tested at a potential scan rate of 0.005 V / s.
[0067] The results showed that the electrolyte had not undergone significant decomposition at around 4.75V, indicating that the electrolyte was suitable for a voltage window range of 0-4.75V.
[0068] Example 2
[0069] A battery comprises the electrolyte obtained in Example 1, a positive electrode and a negative electrode, wherein the positive electrode is a Cu foil and the negative electrode is a lithium sheet.
[0070] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0071] The final test stability cycle number is 130 times.
[0072] Example 3
[0073] A symmetrical battery comprises the electrolyte obtained in Example 1, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0074] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0075] The final test stability cycle number is 500 times.
[0076] Example 4
[0077] A battery comprises the electrolyte obtained in Example 1, a positive electrode and a negative electrode, wherein the positive electrode is LiCoO2 and the negative electrode is lithium, to prepare a LiCoO2-Li battery.
[0078] Performance test: The battery is charged and discharged at a constant current density of 0.5C, and the charge and discharge voltage window is 2.5-4.45V.
[0079] The final tested battery capacity is 151mAh / g and the number of stable cycles is 100 times.
[0080] Comparative Example 1:
[0081] An electrolyte, which is different from Example 1 only in that Compound 1 is not included, and other raw materials and addition amounts are the same as those of Example 1.
[0082] An inert battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a stainless steel gasket and the negative electrode is a stainless steel gasket, and the inert battery is prepared.
[0083] Performance test: The battery was tested at a potential scan rate of 0.005 V / s.
[0084] The final test showed that the electrolyte began to decompose at 3.5V and decomposed rapidly after 4.75V.
[0085] Comparative Example 2:
[0086] A battery comprises the electrolyte obtained in comparative example 1, a positive electrode and a negative electrode, wherein the positive electrode is a Cu foil and the negative electrode is a lithium sheet, and a Li-Cu battery is prepared.
[0087] Performance test: The battery is tested at 0.5 mA / cm2 The charge and discharge are carried out with a current density of 1 h each.
[0088] The final test stability cycle number is 30 times.
[0089] Comparative Example 3
[0090] A symmetrical battery comprises the electrolyte obtained in comparative example 1, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0091] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0092] The final test stability cycle number is 400 times.
[0093] Comparative Example 4
[0094] A battery comprises the electrolyte obtained in Comparative Example 1, a positive electrode and a negative electrode, wherein the positive electrode is LiCoO2 and the negative electrode is lithium, to prepare a LiCoO2-Li battery.
[0095] Performance test: The battery is charged and discharged at a constant current density of 0.5C, and the charge and discharge voltage window is 2.5-4.45V.
[0096] The final tested battery capacity is 110mAh / g and the number of stable cycles is 50 times.
[0097] Example 5
[0098] An electrolyte solution, which is different from Example 1 only in that the electrolyte salt is 0.8M LiPF6, 0.2M LiODFB and 0.4M LiNO3, and the other raw materials and addition amounts are the same as those in Example 1.
[0099] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0100] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0101] The final test stability cycle number is 500 times.
[0102] Example 6
[0103] An electrolyte solution, which is different from Example 5 only in that Compound 1 is replaced by an equal amount of Compound 2 (dimethylamino)difluorosulfonium tetrafluoroborate), and the other raw materials and addition amounts are the same as those in Example 5.
[0104] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0105] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0106] The final test stability cycle number is 350 times.
[0107] Example 7
[0108] An electrolyte solution, which is different from Example 5 only in that compound 1 is replaced by an equal amount of compound 3 (difluoroamino)difluorosulfonium tetrafluoroborate), and other raw materials and addition amounts are the same as those in Example 5.
[0109] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0110] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0111] The final test stability cycle number is 340 times.
[0112] Example 8
[0113] An electrolyte solution, which is different from Example 5 only in that Compound 1 is replaced by an equal amount of Compound 4, and other raw materials and addition amounts are the same as those in Example 5.
[0114] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0115] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0116] The final test stability cycle number is 325 times.
[0117] Example 9
[0118] An electrolyte solution, which is different from Example 5 only in that Compound 1 is replaced by an equal amount of Compound 5, and other raw materials and addition amounts are the same as those of Example 5.
[0119] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0120] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0121] The final test stability cycle number is 320 times.
[0122] Example 10
[0123] An electrolyte solution, which is different from Example 5 only in that Compound 1 is replaced by an equal amount of Compound 6, and other raw materials and addition amounts are the same as those in Example 5.
[0124] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0125] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0126] The final test stability cycle number is 315 times.
[0127] Embodiment 11
[0128] An electrolyte solution, which is different from Example 5 only in that Compound 1 is replaced by an equal amount of Compound 7, and other raw materials and addition amounts are the same as those in Example 5.
[0129] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0130] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0131] The final test stability cycle number is 310 times.
[0132] Example 12
[0133] An electrolyte solution, which is different from Example 5 only in that Compound 1 is replaced by an equal amount of Compound 8, and other raw materials and addition amounts are the same as those in Example 5.
[0134] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0135] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0136] The final test stability cycle number is 350 times.
[0137] Embodiment 13
[0138] An electrolyte solution, which is different from Example 5 only in that Compound 1 is replaced by an equal amount of Compound 9, and other raw materials and addition amounts are the same as those in Example 5.
[0139] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0140] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0141] The final test stability cycle number is 370 times.
[0142] Embodiment 14
[0143] An electrolyte solution, which is different from Example 5 only in that the addition amount of Compound 1 is 0.1wt%, and the other raw materials and addition amounts are the same as those in Example 5.
[0144] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0145] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0146] The final test stability cycle number is 320 times.
[0147] Embodiment 15
[0148] An electrolyte solution, which is different from Example 5 only in that the addition amount of Compound 1 is 0.25wt%, and the other raw materials and addition amounts are the same as those in Example 5.
[0149] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0150] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0151] The final test stability cycle number is 350 times.
[0152] Example 16
[0153] An electrolyte solution, which is different from Example 5 only in that the addition amount of Compound 1 is 0.75wt%, and the other raw materials and addition amounts are the same as those in Example 5.
[0154] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0155] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0156] The final test stability cycle number is 400 times.
[0157] Embodiment 17
[0158] An electrolyte solution, which is different from Example 5 only in that the addition amount of Compound 1 is 1wt%, and the other raw materials and addition amounts are the same as those in Example 5.
[0159] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0160] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0161] The final test stability cycle number is 360 times.
[0162] Embodiment 18
[0163] An electrolyte solution, which is different from Example 5 only in that the volume ratio of solvents TGDME, FEC and TTFB is 8:1:1, and other raw materials and addition amounts are the same as those in Example 5.
[0164] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0165] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0166] The final test stability cycle number is 400 times.
[0167] Embodiment 19
[0168] An electrolyte solution, which is different from Example 5 only in that the volume ratio of solvents TGDME, FEC and TTFB is 7:1:2, and other raw materials and addition amounts are the same as those in Example 5.
[0169] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0170] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0171] The final test stability cycle number is 450 times.
[0172] Embodiment 20
[0173] An electrolyte, which is different from Example 5 only in that LiNO3 is not included, and other raw materials and addition amounts are the same as those in Example 5.
[0174] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0175] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0176] The final test stability cycle number is 300 times.
[0177] Embodiment 21
[0178] An electrolyte, which is different from Example 5 only in that LiODFB is not included, and other raw materials and addition amounts are the same as those in Example 5.
[0179] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a lithium sheet and the negative electrode is a lithium sheet, and a Li-Li symmetrical battery is prepared.
[0180] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0181] The final test stability cycle number is 320 times.
[0182] Embodiment 22
[0183] An electrolyte solution, which is different from Example 5 only in that the electrolyte salt is 0.8M NaPF6, 0.2M NaODFB and 0.4 NaNO3, and the other raw materials and addition amounts are the same as those in Example 5.
[0184] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a sodium foil and the negative electrode is a sodium foil, and a Na-Na symmetrical battery is prepared.
[0185] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0186] The final test stability cycle number is 600 times.
[0187] Comparative Example 5
[0188] An electrolyte, which differs from Example 22 only in that it does not include Compound 1, and other raw materials and addition amounts are the same as Example 22.
[0189] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a sodium foil and the negative electrode is a sodium foil, and a Na-Na symmetrical battery is prepared.
[0190] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0191] The final test stability cycle number is 300 times.
[0192] Embodiment 23
[0193] An electrolyte solution, which is different from Example 5 only in that the electrolyte salt is 0.8M KPF6, 0.2M KODFB and 0.4M KNO3, and the other raw materials and addition amounts are the same as those in Example 5.
[0194] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a potassium foil and the negative electrode is a potassium foil, and a KK symmetrical battery is prepared.
[0195] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0196] The final test stability cycle number is 540 times.
[0197] Comparative Example 6
[0198] An electrolyte, which differs from Example 23 only in that it does not include Compound 1, and other raw materials and addition amounts are the same as Example 23.
[0199] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a potassium foil and the negative electrode is a potassium foil, and a KK symmetrical battery is prepared.
[0200] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0201] The final test stability cycle number is 300 times.
[0202] Embodiment 24
[0203] An electrolyte solution, which is different from Example 5 only in that the electrolyte salt is 0.8M ZnPF6, 0.2M ZnODFB and 0.4 ZnNO3, and the other raw materials and addition amounts are the same as those in Example 5.
[0204] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a zinc foil and the negative electrode is a zinc foil, and a Zn-Zn symmetrical battery is prepared.
[0205] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0206] The final test stability cycle number is 1000 times.
[0207] Comparative Example 7
[0208] An electrolyte, which differs from Example 24 only in that it does not include Compound 1, and other raw materials and addition amounts are the same as Example 24.
[0209] A symmetrical battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode is a zinc foil and the negative electrode is a zinc foil, and a Zn-Zn symmetrical battery is prepared.
[0210] Performance test: The battery is tested at 0.5 mA / cm 2 The charge and discharge are carried out with a current density of 1 h each.
[0211] The final test stability cycle number is 400 times.
[0212] It can be seen from the above Examples 1-27 that adding the compound shown in structural formula I to the electrolyte can significantly increase the stable cycle times of the battery; at the same time, the compound shown in structural formula I can play a good role in improving the stable cycle times of the battery in the range of 0.1-30wt%. Compared with the control example without adding electrolyte additives, the cycle performance of the Li-Li, Na-Na, KK, and Zn-Zn symmetrical batteries in the embodiments of the present invention is significantly improved.
[0213] Embodiment 25
[0214] A method for preparing a Li-LiCoO2 secondary battery, wherein the electrolyte is the electrolyte obtained in Example 6, comprising the following steps:
[0215] LiCoO2, Super P and a NMP mixture containing 1% PVDF by mass were mixed in a mass ratio of LiCoO2:Supp P:PVDF=8:1:1, and the mixture was shaken with a high-speed shaker to obtain a slurry. The slurry was coated on an aluminum foil, and then vacuum dried at a temperature of 60-80°C for 12 hours to obtain a pole piece. The pole piece was cut into a disc with a diameter of 12 mm using a mold as the positive electrode material of the Li-LiCoO2 secondary battery, and a lithium foil with a diameter of 16 mm was used as the negative electrode material. The battery was assembled using a separator with model number Cegard2400.
[0216] Performance test: The battery was charged and discharged at a current density of 0.2C.
[0217] The final tested battery capacity is 130mAh / g and the number of stable cycles is 80 times.
[0218] Embodiment 26
[0219] A method for preparing a Li-LiCoO2 secondary battery is different from Example 25 only in that the electrolyte is the electrolyte obtained in Example 7. The remaining steps and process parameters are the same as those in Example 25.
[0220] Performance test: The battery was charged and discharged at a current density of 0.2C.
[0221] The final tested battery capacity is 131mAh / g and the number of stable cycles is 78 times.
[0222] Embodiment 27
[0223] A method for preparing a Li-LiCoO2 secondary battery is different from Example 25 only in that the electrolyte is the electrolyte obtained in Example 8. The remaining steps and process parameters are the same as those in Example 25.
[0224] Performance test: The battery was charged and discharged at a current density of 0.2C.
[0225] The final tested battery capacity is 132mAh / g and the number of stable cycles is 60 times.
[0226] Embodiment 28
[0227] A method for preparing a Li-LiCoO2 secondary battery is different from Example 25 only in that the electrolyte is the electrolyte obtained in Example 9. The remaining steps and process parameters are the same as those in Example 25.
[0228] Performance test: The battery was charged and discharged at a current density of 0.2C.
[0229] The final tested battery capacity is 105mAh / g and the number of stable cycles is 85 times.
[0230] Embodiment 29
[0231] A method for preparing a Li-LiCoO2 secondary battery is different from Example 25 only in that the electrolyte is the electrolyte obtained in Example 10. The remaining steps and process parameters are the same as those in Example 25.
[0232] Performance test: The battery was charged and discharged at a current density of 0.2C.
[0233] The final tested battery capacity is 135mAh / g and the number of stable cycles is 60 times.
[0234] Embodiment 30
[0235] A method for preparing a Li-LiCoO2 secondary battery is different from Example 25 only in that the electrolyte is the electrolyte obtained in Example 11. The remaining steps and process parameters are the same as those in Example 25.
[0236] Performance test: The battery was charged and discharged at a current density of 0.2C.
[0237] The final tested battery capacity is 142mAh / g and the number of stable cycles is 70 times.
[0238] Embodiment 31
[0239] A method for preparing a Li-LiCoO2 secondary battery, which is different from Example 25 only in that the electrolyte is the electrolyte obtained in Example 12. The remaining steps and process parameters are the same as those in Example 25.
[0240] Performance test: The battery was charged and discharged at a current density of 0.2C.
[0241] The final tested battery capacity is 123mAh / g and the number of stable cycles is 70 times.
[0242] Embodiment 32
[0243] A method for preparing a Li-LiCoO2 secondary battery is different from Example 25 only in that the electrolyte is the electrolyte obtained in Example 13. The remaining steps and process parameters are the same as those in Example 25.
[0244] Performance test: The battery was charged and discharged at a current density of 0.2C.
[0245] The final tested battery capacity is 131mAh / g and the number of stable cycles is 75 times.
[0246] Embodiment 33
[0247] A method for preparing a Na-NaCoO2 secondary battery, wherein the electrolyte is the electrolyte obtained in Example 22, comprising the following steps:
[0248] NaCoO2, PVDF and spuer P are mixed in a mass ratio of 8:1:1, and NMP with a mass 5 times that of the above solid is added, and a slurry is obtained by a high-speed oscillator. The obtained slurry is coated on an aluminum foil, and then vacuum dried at a temperature of 60-80°C for 12 hours to obtain a pole piece, and the pole piece is cut into a disc with a diameter of 12 mm using a mold as the positive electrode material of the Na-NaCoO2 secondary battery, and a sodium metal foil with a diameter of 16 mm is used as the negative electrode material, and the battery is assembled using a separator with model Cegard 2400.
[0249] Performance test: The battery was charged and discharged at a current density of 0.2C.
[0250] The final tested battery capacity is 135mAh / g and the number of stable cycles is 80 times.
[0251] Comparative Example 8
[0252] A method for preparing a Na-NaCoO2 secondary battery, which is different from Example 33 only in that the electrolyte is the electrolyte obtained in Example 23. The remaining steps and process parameters are the same as those in Example 33.
[0253] Performance test: The battery was charged and discharged at a current density of 0.2C.
[0254] The final tested battery capacity is 121mAh / g and the number of stable cycles is 60 times.
[0255] Embodiment 34
[0256] A method for preparing a K-KCoO2 secondary battery, wherein the electrolyte is the electrolyte obtained in Example 24, comprising the following steps:
[0257] KCoO2, PVDF and spuerP were mixed in a mass ratio of 8:1:1, and NMP with a mass 5 times that of the above solids was added, and a slurry was obtained by a high-speed oscillator. The obtained slurry was coated on an aluminum foil, and then vacuum dried at a temperature of 60-80°C for 12 hours to obtain a pole piece. The pole piece was cut into a disc with a diameter of 12 mm using a mold as the positive electrode material of the K-KCoO2 secondary battery, and a potassium metal foil with a diameter of 16 mm was used as the negative electrode material. The battery was assembled using a separator with model number Cegard 2400.
[0258] Performance test: The battery was charged and discharged at a current density of 0.2C.
[0259] The final tested battery capacity is 125mAh / g and the number of stable cycles is 70 times.
[0260] Comparative Example 9
[0261] A method for preparing a K-KCoO2 secondary battery, which is different from Example 34 only in that the electrolyte is the electrolyte obtained in Example 25. The remaining steps and process parameters are the same as those in Example 34.
[0262] Performance test: The battery was charged and discharged at a current density of 0.2C.
[0263] The final tested battery capacity is 121mAh / g and the number of stable cycles is 40 times.
[0264] Embodiment 35
[0265] A method for preparing a Zn-Zn(CoO2)2 secondary battery, wherein the electrolyte is the electrolyte obtained in Example 26, comprising the following steps:
[0266] Zn-Zn(CoO2)2, PVDF and spuerP are mixed in a mass ratio of 8:1:1, and NMP with a mass 5 times that of the above solids is added, and a slurry is obtained by a high-speed oscillator. The obtained slurry is coated on an aluminum foil, and then vacuum dried at a temperature of 60-80°C for 12 hours to obtain an electrode. The electrode is cut into discs with a diameter of 12 mm using a mold as the positive electrode material of the Zn-Zn(CoO2)2 secondary battery, and a Zn metal foil with a diameter of 16 mm is used as the negative electrode material. The battery is assembled using a separator of model Cegard 2400.
[0267] Performance test: The battery was charged and discharged at a current density of 0.2C.
[0268] The final tested battery capacity is 125mAh / g and the number of stable cycles is 70 times.
[0269] Comparative Example 10
[0270] A method for preparing a Zn-Zn(CoO2)2 secondary battery, which is different from Example 35 only in that the electrolyte is the electrolyte obtained in Example 27. The remaining steps and process parameters are the same as those in Example 35.
[0271] Performance test: The battery was charged and discharged at a current density of 0.2C.
[0272] The final tested battery capacity is 121mAh / g and the number of stable cycles is 40 times.
[0273] As shown in Examples 25-35, the electrolyte additive of the present invention can achieve a relatively high stable cycle number of the battery under different solvent compositions, electrolyte salt types and electrode materials. And as shown in Examples 33-35 and Comparative Examples 8-10, when the additive is applied to Na-NaCoO2, K-KCoO2, and Zn-Zn(CoO2)2 batteries, the addition of the compound shown in Structural Formula I can still significantly increase the stable cycle number of the battery. As shown in Example 4 and Comparative Example 4, the addition of the compound shown in Structural Formula I can effectively improve the cycle performance of Li-LiCoO2 batteries.
[0274] The electrolytes of Example 2 and Comparative Example 2 were used in Li-Cu batteries at 0.5 mA / cm 2 At a current density of 1.5, the deposition and stripping were performed for 1 hour each, and the coulombic efficiency of the battery during the charge and discharge cycle was tested. The results are as follows: Figure 2 As shown, Figure 1 The horizontal axis is the number of cycles, and the vertical axis on the left is the coulomb efficiency (%). Figure 2 It can be seen that for the battery without compound 1, the coulombic efficiency of the battery drops rapidly after 10 cycles, while for the battery with compound 1, the coulombic efficiency remains above 98% after 120 cycles, and the cycle performance is greatly improved, indicating that the use of electrolyte with compound 1 can effectively improve the interface condition of the battery and inhibit the growth of lithium dendrites in the battery.
[0275] The electrolytes of Example 3 and Comparative Example 3 were used to prepare Li-Li symmetric batteries at 0.5 mA / cm 2 The current density is set to 1h for charge and discharge, and the time-voltage curve obtained by the test is as follows Figure 3 As shown, from Figure 3 It can be seen that for the electrolyte without DDTB, the voltage increases sharply after 800 h of cycling, while after adding DDTB, the voltage curve remains stable after 1000 h of cycling, indicating that DDTB can effectively improve the stability of Li-Li symmetric batteries.
[0276] The electrolytes of Example 4 and Comparative Example 4 were used to prepare Li-LiCoO2 batteries, and the batteries were charged and discharged at a current density of 0.5C, with a charge and discharge voltage of 2.5-4.45V. The time-voltage curves obtained by the test were as follows: Figure 4 As shown, from Figure 5 It can be seen that for the electrolyte without DDTB, the battery capacity decays rapidly after 20 cycles, while after adding DDTB, the battery capacity begins to decay rapidly after 80 cycles, indicating that DDTB can effectively improve the cycle performance of Li-LiCoO2 batteries.
[0277] After the batteries of Example 3 and Comparative Example 3 were cycled 50 times, they were tested using SEM. Figure 4 Part a is a SEM image of the Li-Li symmetric battery in Comparative Example 3 after 100 cycles. It can be seen that there are many fibrous lithium dendrites on the electrode surface, indicating that the growth of lithium dendrites cannot be effectively inhibited in this system without adding additives. Figure 4 Part b is a SEM image of the lithium electrode using the electrolyte in Example 3. It can be seen that the lithium deposition on the surface of the electrode in the electrolyte with DDTB added is dense and uniform, and no obvious dendrites appear, indicating that the use of DDTB can effectively inhibit the growth of lithium dendrites.
[0278] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A use of a fluorine-containing onium salt in an electrolyte additive, characterized in that: The structure of the fluorine-containing onium salt is shown in formula (1): Wherein, R1 and R2 are independently selected from hydrocarbon groups, F or fluorine-substituted hydrocarbon groups.
2. An electrolyte additive, characterized in that: The invention comprises the fluorine-containing onium salt as claimed in claim 1.
3. Use of the electrolyte additive as claimed in claim 2 in preparing an electrolyte.
4. An electrolyte, characterized in that: The invention comprises a solvent, an electrolyte salt and the electrolyte additive according to claim 2.
5. The electrolyte according to claim 2, characterized in that Based on the total mass of the electrolyte being 100%, the content of the electrolyte additive is 0.1-30wt%.
6. The electrolyte according to claim 3, characterized in that The solvent includes ether solvents, carbonate solvents and borate solvents.
7. The electrolyte according to claim 3, characterized in that The electrolyte salt includes MPF6, MBF4, MODFB, MBOB, MClO4, MNO3, MCF3SO3, MODFP, MN(SO2CF3)2, MN(SO2F)2, MHFDF, MTFSI 、 One or any combination of MFSIs; Wherein, the M is one of Li, Na and K.
8. Use of the electrolyte additive according to claims 4 to 7 in the preparation of secondary batteries.
9. A secondary battery, characterized in that: The electrolyte comprising any one of claims 4 to 7.
10. The secondary battery according to claim 9, characterized in that: The positive electrode material, the negative electrode material or the electrolyte of the secondary battery includes lithium element.